Identification of Causes and The Existence of Mercury and Chromium in Sediment and Sea Water in Kendari Bay - Damayanty, Sri; Kamal, Muhammad; Pawennari Muhammad, Arief (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Kendari Bay is currently experiencing considerable physical pressure and pollution due to heavy metals. This study aims to determine the content of heavy metals mercury and chromium in sediment and seawater in Kendari Bay. This study uses an observational design with a descriptive approach. The study was conducted in April 2019 in five Port areas with three sampling points in each region. Samples taken are sediment and seawater. Samples taken were analyzed by the Atomic Absorption Spectrophotometry (AAS) method. The results show that all sampling points at five Ports have been contaminated with mercury and chromium in sediment and seawater. The levels of mercury and chromium have exceeded the quality standards stipulated by Minister of Environment Decree No. 51 of 2004. The highest levels of mercury and chromium in seawater and sediment are highest in the Dermaga Tempat Pendaratan Ikan (TPI). This is due to the dense traffic activity of fishing vessels, residential waste, Hospital waste, hospitality waste, tourist waste, paints on ships, oil spills, rust from shipwrecks, and heavy equipment activities from the construction of the Bahteramas Bridge or the Kendari Bay Bridge. Technology needs to control heavy metal contamination as well as policies and law enforcement regarding activities at sea that have the potential to pollute waters.